Advanced Accounting Problems/Workbook to accompany Advanced Accounting Problems (Book). - newcomer, Hale L. (The Accounting Review, 1959)
Reviews two books. "Advanced Accounting Problems-Theory and Practice" and "Workbook to Accompany Advanced Accounting Problems," by Irving J. Chaykin and Max Zimering